FILM ANIMASI ‘RIKO THE SERIES: EPISODE TANAMAN BERTASBIH’ (Kajian Living Qur`an) - Muhammad Taufiq; Ahmad Mustofa (Institut Agama Islam Syubbanul Wathon Magelang, 2023)
This article intends to identify the form of the reception of the Qur'an contained in the 20th episode of the animated film Riko The Series entitled